A new PCR assay based on the new gene-SPUL_2693 for rapid detection of Salmonella enterica subsp. enterica serovar Gallinarum biovars Gallinarum and Pullorum. (7th August 2018) - Xu, Ying; Hu, Yachen; Guo, Yaxin; Zhou, Zihao; Xiong, Dan; Meng, Chuang; Li, Qiuchun; Geng, Shizhong; Pan, Zhiming; Jiao, Xinan
ABSTRACT: Salmonella enterica subsp . enterica serovar Gallinarum biovar Gallinarum ( S . Gallinarum) and biovar Pullorum ( S . Pullorum) are gram-negative bacteria, members of the most important infectious pathogens, and have caused common problems in the poultry industry, especially in the developing countries. O- and H-antigen specific anti-sera are commonly for slide and tube agglutination tests to identify Salmonella serovars. However, it is both labor intensive and time consuming, so there is an urgent need for a new technique for the rapid detection of the major Salmonella serovars. In this study, we developed a 1-step PCR assay to identify the serovar Gallinarum. This PCR-based assay was based on the SPUL_2693 gene, which was located in SPI-19 and found by comparing the genomes of the S . Pullorum and S . Gallinarum in the whole data of NCBI. The specificity of this gene was evaluated by bioinformatics analysis, and the results showed that the SPUL_2693 gene exists in all serovar Gallinarum. The specificity and sensitivity of this PCR assay were evaluated in our study. The developed PCR assay was able to distinguish the serovar Gallinarum from 27 different Salmonella serovars and 5 different non- Salmonella pathogens. The minimum limit of genomic DNA of S. Pullorum for PCR detection was 2.143 pg/μL, and the minimum limit number of cells was 6 CFU. This PCR assay was also applied to analyze Salmonella strains isolated from a chicken farm in this study. The PCR assay properly identified the serovar Gallinarum from other Salmonella serovars, and the results were in agreement with the results of a traditional serotyping assay. In general, the newly developed PCR-based assay can be used to accurately judge the presence of the serovar Gallinarum and can be combined with traditional serotyping assays, especially in the case of large quantities of samples.